If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = -3 + 5x Reorder the terms: 7 + 2x = -3 + 5x Solving 7 + 2x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + 2x + -5x = -3 + 5x + -5x Combine like terms: 2x + -5x = -3x 7 + -3x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + -3x = -3 + 0 7 + -3x = -3 Add '-7' to each side of the equation. 7 + -7 + -3x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -3 + -7 -3x = -3 + -7 Combine like terms: -3 + -7 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333
| 5x+15=3x+8+2x-7 | | 3y-13+2y-12=180 | | 2t-83+2t-51=180 | | 14y-6=5 | | 5x-2=-x-32 | | -3r+20=15r-8 | | 11x+11+9x-11=180 | | 2t-51+2t-83=180 | | 11x+11+2y-12=180 | | 6x-7=53-4x | | 8x+4y=52 | | 2x+7=8(4+x) | | 2q-88+q+58=180 | | 2x+7=8(4+6) | | 0.3(n+4)=5 | | 90=6x-1 | | -3+4x=3x-15 | | -8+4x=6x+0 | | -4-2x-5x=80 | | 4u-42=-2(u-3) | | 6-3(1+8k)=33 | | 3(c+11)=45 | | 2msquare-50=0 | | y+7=-3(x-6) | | 6x-(4y)=8 | | B=6y-20 | | 1059.0592=38.936*w | | xy+3y=-4 | | 31=8x | | 8a-11=3a+4 | | 1300.4624=2*120.7016+L | | 8(x-4)-(2x+4)=20 |